Acclimation potential of Noni (Morinda citrifolia L.) plant to temperature stress is mediated through photosynthetic electron transport rate. (4th March 2021) - Gupta, Ramwant; Sharma, Ravi D.; Rao, Yalaga R.; Siddiqui, Zahid H.; Verma, Amit; Ansari, Mohammad W.; Rakwal, Randeep; Tuteja, Narendra
ABSTRACT: Noni ( Morindacitrifolia L.), a tropical, medicinal plant of the family Rubiaceae utilized since 2000 y ago by the Polynesians, is currently facing a major challenge in production vis-a-vis climate change. The worldwide average temperatures continue to fluctuate, resulting in extremely cold winters and hot summers that reduce plant productivity. Photosynthetic apparatus is an exceptionally sensitive component to estimate the degree of damage at contrasting temperatures. The present study was aimed to evaluate the temperature stress response of Noni plant using the chlorophyll a fluorescence OJIP transients (OJIP transients). Results showed the declined photosynthetic pigment pool and reduced functional and structural integrity of the photosynthetic apparatus under very low- and high-temperature treatments. Drastically lower yield parameters such as φ(Po) and φ(Eo), efficiency ψ(Eo) and performance indices – PIabs and PItotal, and accumulation of inactive reaction centers were observed. Consecutively, a lower level of calculated electron transport from PSII to PSI was observed. In contrast, the enhanced δRo indicates that PSI is more thermo-tolerant as compared to PSII. Additionally, very low and high temperatures cause an increase in antenna size (ABS/RC) and the decrease in the amplitude of I to P phase of fluorescence transient. Overall, the photosynthetic apparatus of leaf tissue was more sensitive to low and high temperatures than the developing fruit. The findings of the present study demonstrated the potential role of thylakoid components of the photosynthetic apparatus, which might be crucial in regulating the temperature stress response in the Noni plant, and thereby crop improvement.